Bull-leaping in the ancient Near East - Dijk-Coombes, Renate M. van (Journal for semitics, 2013)
Depictions of bull-leaping are found in Middle Bronze Age art of the late third- to the mid-second millennium BCE in Egypt, Anatolia, the Levant, and on Minoan Crete. Four main types of bull-leap can be identified: the "classic type", the "schema of the diving leaper", the "schema of the floating leaper", and a fourth type which involved passing beneath the bull. The bull-leaping depictions are compared to the recortes (a type of bull-sport practised in some parts of modern-day Spain) in order to identify which of the visual representations could have been executed by ancient Near Eastern leapers. These depictions will further be analysed and compared to determine if the peoples of the ancient Near East were familiar with and had first-hand knowledge of bull-leaping, and whether it ever occurred as a practice in any area of the ancient Near East.